Pengaruh Budaya Organisasi dan Pengendalian Internal terhadap Pencegahan Korupsi dengan Good Governance sebagai Intervening (Studi Pada BPJS Ketenagakerjaan) - Rastasari, Tania (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2024)
With the greater amount of trust funds being managed, the greater the risks faced, one of which is the risk of corruption. Therefore, the management of funds must be carried out in a transparent, accountable manner, prioritizing the principles of prudence and good governance. This study aims to examine how organizational culture and internal control affect corruption prevention with Good Governance as intervening. Respondent data uses the results of distributing questionnaires to permanent employees of BPJS Ketenagakerjaan who have more than 5 years of service and hold structural positions or have held structural positions placed at the Head Office, Regional Offices and Branch Offices. The sampling method uses purposive sampling. In accordance with the theoretical model and hypotheses proposed, then tested by the SEM PLS method using the SmartPLS version 4.0 software application including outer model, inner model, and hypothesis testing. The results of this study indicate that: 1. Organizational Culture has a positive effect on Corruption Prevention 2. Internal Control has a positive effect on Corruption Prevention 3. Organizational Culture has a positive effect on Good Governance 4. Internal Control has a positive effect on Good Governance 5. Good Governance has a positive effect on Corruption Prevention 6. Organizational Culture has an effect on Corruption Prevention through Good Governance 7. Internal Control has a positive effect on Corruption Prevention through Good Governance. The proof of these seven hypotheses shows that building a strong organizational culture, effective internal control and implementing Good Governance consistently and continuously can help organizations achieve their goals while increasing corruption prevention efforts. Through this research, it is hoped that it can provide positive implications theoretically and provide new references for researchers who have similar topic interests in order to improve the quality of future research.